2020
DOI: 10.1186/s12881-020-01133-8
|View full text |Cite
|
Sign up to set email alerts
|

p.Arg72Pro polymorphism of P53 and breast cancer risk: a meta-analysis of case-control studies

Abstract: Background The effect of the p.Arg72Pro variant of the P53 gene on the risk of development ofbreast cancer remains variable in populations. However, the use ofstrategies such aspoolingage-matched controls with disease may provide a consistent meta-analysis. Our goal was to perform a meta-analysis in order to assess the association of p.Arg72Pro variant of P53 gene with the risk of breast cancer. Methods Databases such as PubMed, Gene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 65 publications
(81 reference statements)
2
14
0
Order By: Relevance
“…The results of the published meta-analyses on the association between TP53 codon 72, IVS3 16 bp, and IVS6+62A > G polymorphisms and BC risk in different ethnic groups are shown in Supplementary Table S5 and the cells highlighted with red color indicated significant results. Two studies ( Dunning et al, 1999 ; Diakite et al, 2020b ) showed that the codon 72 polymorphism increased BC risk in overall analysis. In the ethnic subgroup analyses of the association between codon 72 polymorphism and BC risk, one study ( Gonçalves et al, 2014 ) found that the polymorphism significantly increased BC risk in Asians, and another study ( Diakite et al, 2020b ) indicated an obviously increased BC risk in Caucasians.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The results of the published meta-analyses on the association between TP53 codon 72, IVS3 16 bp, and IVS6+62A > G polymorphisms and BC risk in different ethnic groups are shown in Supplementary Table S5 and the cells highlighted with red color indicated significant results. Two studies ( Dunning et al, 1999 ; Diakite et al, 2020b ) showed that the codon 72 polymorphism increased BC risk in overall analysis. In the ethnic subgroup analyses of the association between codon 72 polymorphism and BC risk, one study ( Gonçalves et al, 2014 ) found that the polymorphism significantly increased BC risk in Asians, and another study ( Diakite et al, 2020b ) indicated an obviously increased BC risk in Caucasians.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies ( Dunning et al, 1999 ; Diakite et al, 2020b ) showed that the codon 72 polymorphism increased BC risk in overall analysis. In the ethnic subgroup analyses of the association between codon 72 polymorphism and BC risk, one study ( Gonçalves et al, 2014 ) found that the polymorphism significantly increased BC risk in Asians, and another study ( Diakite et al, 2020b ) indicated an obviously increased BC risk in Caucasians. With respect to the TP53 IVS3 16 bp polymorphism, 6 studies ( Dunning et al, 1999 ; Hu et al, 2010a ; Hu et al, 2010b ; He et al, 2011 ; Sagne et al, 2013 ; Wu et al, 2013 ; Diakite et al, 2020a ) found an obviously increased BC risk in overall analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations